ANALISIS PERBANDINGAN MINAT KONSUMEN DALAM MELAKUKAN PEMBELIAN KOSMETIK BERLABEL HALAL DENGAN KOSMETIK TANPA LABEL HALAL - Afrianti, Resa; Suprianto, S (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to determine the difference in consumer interest in buying cosmetics with a halal label and cosmetics without a halal label. The type of this study was comparative study used to compare consumer interest in buying cosmetics with a halal label and cosmetics without a halal label. The type of data used was quantitative data obtained directly from respondents using an instrument in the form of a questionnaire. Respondents in this study were students from Samawa University, Sumbawa Besar who had purchased cosmetics with halal labels and without halal labels, totaling 100 people. The sampling technique in this study used a non-probability sampling technique with the accidental sampling (convenience sampling) method. The data analysis in this study used the two-average difference test technique, including the Kolmogorov Smirnov normality test, paired samples statistics test, paired samples correlations test, and paired samples test. The results of this study showed that there was a positive and significant difference in consumer interest in buying cosmetics with a halal label and cosmetics without a halal label. Consumers are more interested in buying cosmetics with a halal label compared to cosmetics without a halal label. Thus, it can be stated that providing halal labels on cosmetic product packaging had a big impact on increasing consumer interest in buying cosmetics.